Training and overtraining: an introduction - Kuipers, H. (Medicine & Science in Sports & Exercise, 1998)
Elite sport requires high training volumes. However, little is known about the relationship between training volume and performance development. This relationship appears to have an inverted U-shape. Short-term overtraining or overreaching is probably associated with insufficient metabolic recovery, resulting in a decline in ATP levels. Systemic overtraining or staleness is attributed to failure of the hypothalamus to cope with the total amount of stress. Clinically, a parasympathetic and sympathetic form has been distinguished. It is assumed that these two forms express different stages of staleness. No specific, simple, and reliable parameters are known to diagnose overreaching and overtraining in the earliest stage.